Volvo 2040: Framtidens kylsystem har aldrig varit Coolare - Asal, Josef; Ekblad, Matilda; Feldt, Axel; Svärd, Maja; Wallenfeldt, Victoria; Walter, Jacob (My University, 2024)
A major challenge for the company of Volvo Group is the evolving technology, as well as remaining relevant inrelation to their competitors’ progress and their customers’ increasing expectations. As of now more and more new competitors are posing a challenge that Volvo Group previously didn’t have to consider. As a result of this, Volvo Group is expressing a desire to widen their market to stay at the forefront and meet both current and future customers’ demands. The purpose of the project is to explore new areas where Volvo Group can enhance its competitiveness by creating innovative and sustainable solutions relevant to the year 2040. Volvo Group mainly sought after a solution that has a direct link to their current business, but at the same time isn’t a further developed version of something they already offer. The purpose is to explore new areas where Volvo Group can strengthen its competitiveness by developing innovative and sustainable concepts relevant to the year 2040. Based on the performed research, it was apparent that within cold chain transportation there’s a lot of waste, and there are possibilities within this field for Volvo Group to expand. The final concept that was created is an integrated cooling system in the truck which is able to control the temperature in both the cab and the trailer. Instead of having a system which controls the cab’s temperature, and another, external, system that controls the temperature of the trailer they’re merged as one. The energy source for the system would be the trucks’ own battery instead of a diesel engine (which is currently in use). Additionally, the system is more lightweight than the current systems which makes it cheaper for the customer in the long run. This concept isn’t fully developed, and would need more development before Volvo Group would be able to offer it as a part of their product.